Development of efficient designs of cooking systems. II. Computational fluid dynamics and optimization - Joshi, J.; Pandit, A.; Patel, S.; Singhal, R.; Bhide, G.; Mariwala, K.; Devidayal, B.; Danao, S.; Ganguli, A.; Gudekar, A.; Chavan, P.; Shinde, Yogesh (2012)
Sections 2-6 of Part I were devoted to the analysis of heat transfer characteristics of cookers. In all the experiments, only water was employed as a working medium. Now, we extend such an analysis to the actual cooking process in order to arrive at an improved cooking device. The major strategies for the optimization of energy utilization is to design appropriate insulation that has been obtained by two cover vessels. In order to select an air gap, the flow and temperature patterns in the air gap have been extensively analyzed using computational fluid dynamics (CFD). The flow pattern and heat transfer in cooking pots have also been analyzed by CFD. This has enabled us to design suitable internals for minimizing the stratification of temperature. The understanding of fluid mechanics has also given basis for selection of heat flux, gap between burner tip and cooker bottom, and temperature of flue gases leaving the cooker. Chemical engineering principles have been used for modeling and optimization. Kinetics have been obtained in batch cookers. The knowledge of kinetics, thermal mixing, axial mixing, and optimum selection of insulation have been employed for the development of continuous cookers. The continuous mode of operation also helps in saving of energy. Systematic data have been collected for the design and scale up of continuous cookers. © 2011 American Chemical Society.